« L’avis des nuiteux » - Marion Guenot (Temporalités)
This contribution offers a brief overview of the issues of night work in the police, through depictions of situations and agents working in anti-crime brigades (BAC) and emergency police, ensuring a human presence 24 hours a day and 7 days a week. It also explore union and association demands, recent because they only started to occur in the mid-2010s. How did these agents come to mobilize and make their demands heard, both with their unions and with the authorities public? What are, on a daily basis, the more informal negotiations and adaptations that can be observed in this singular way of life and work ?